2020
DOI: 10.3389/fnins.2020.00510
|View full text |Cite
|
Sign up to set email alerts
|

In vivo MRI Successfully Reveals the Malformation of Cortical Development in Infant Rats

Abstract: Objective: Malformations of cortical development (MCDs) are major causes of intractable epilepsies. To characterize the early neuroimaging findings of MCDs, we tried to identify the MRI features consistent with pathological findings in an infant rat MCD model, prenatally exposed to methylazoxymethanol (MAM), by using newly developed MRI techniques. Methods: At gestational day 15, two doses of MAM (15 mg/kg intraperitoneally) or normal saline were injected into pregnant rats. The offspring underwent in vivo MRI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 53 publications
2
5
0
Order By: Relevance
“…Toxic effects limit the application of Mn 2+ as an exogenous contrast in humans, thereby hampering its use for the diagnosis of FCD, and fostering the use of endogenous sources of contrast for the study of cortical layering. In a rodent model of FCD that shares similarities with the one used here ( 49 ) reductions of FA were found in white matter structures, as well as in the retrosplenial and cingulate cortices that are consistent with our findings ( Figure 3 ). In their study, alterations of cortical layering and hypomyelination were also identified.…”
Section: Discussionsupporting
confidence: 90%
“…Toxic effects limit the application of Mn 2+ as an exogenous contrast in humans, thereby hampering its use for the diagnosis of FCD, and fostering the use of endogenous sources of contrast for the study of cortical layering. In a rodent model of FCD that shares similarities with the one used here ( 49 ) reductions of FA were found in white matter structures, as well as in the retrosplenial and cingulate cortices that are consistent with our findings ( Figure 3 ). In their study, alterations of cortical layering and hypomyelination were also identified.…”
Section: Discussionsupporting
confidence: 90%
“…Quantitative proteome analysis revealed that synaptogenesis signaling was the most signi cantly downregulated canonical pathway in the malformed cortex of prenatal rats exposed to MAM at P15 (Table S1), consistent with the decrease in CaMKIIA along with an increase in the susceptibility to NMDAinduced spasms [5]. Our previous work demonstrated the poor dendritic spine development and reduced neuronal population in the RSC of prenatally MAM-exposed rats [12]. Altered early synaptogenesis is reported in neurodevelopmental disorders, including epilepsy, intellectual disability, and autism spectrum disorders [28].…”
Section: Discussionsupporting
confidence: 74%
“…In particular, the reduced activity of CaMKII is known to be related to epilepsy [31,32]. This decreased expression of cortical CaMKII in malformed brain may be related to the previously reported dendritic arborization [12] and increased spasm susceptibility [5].…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations